A Multimodal Hand Recognition System Based on Finger Inner-Knuckle Print and Finger Geometry. Issue 1 (2nd January 2019) - Bahmed, Farah; Mammar, Madani Ould; Ouamri, Abdelaziz
Abstract: Security applications based on hand biometrics are good mean for personal authentication and access control. This article proposes a novel multimodal biometric system that makes use of hand fingers' inner knuckle prints and hand's fingers' geometry. Further, both major knuckle print and minor knuckle print are used. A statistical approach for finger geometry features selection is also proposed. Biometric fusion is investigated using different strategies. Experimental results obtained on a contactless database using standard metrics show that the proposed system achieves high recognition rate. Thus, the proposed approach achieves effective authentication accuracy and can be used in real conditions.